The Effectiveness of the SAVI Learning Model in Improving Students’ Metacognitive and Critical Thinking Skills in MAN Kota Magelang - Hasan, Salwaa Fauziyyah; Darmawan, Ericka; Sukmawati, Ika (Biosfer: Jurnal Tadris Biologi, 2023)
This study aims to determine the effectiveness of the SAVI (Somatic, Auditory, Visualization, and Intellectual) learning model on students' metacognitive and critical thinking skills. The SAVI model has four stages: preparation, delivery, training, and results display. The researchers chose imagery and metaphor to convey material about the circulatory system in humans. This research is a quasi-experimental study with the Nonequivalent Control Group Design. The SAVI model is applied to the experimental class. Data collection was carried out by pretest and posttest to assess the improvement of these two skills. The test used is the independent sample t-test and normalized gain. The results showed significant differences in improving metacognitive and critical thinking skills between students in the experimental and control classes (0.00 <0.05). The SAVI model is also quite effective in improving these two skills, with an N-Gain of 51.58% and 62.41%, respectively.ABSTRAK: Penelitian ini bertujuan untuk mengetahui efektivitas model pembelajaran SAVI (Somatic, Auditory, Visualization, and Intellectual) terhadap keterampilan metakognitif dan berpikir kritis peserta didik. Model SAVI memiliki empat tahapan yaitu persiapan, penyampaian, pelatihan dan penampilan hasil. Peneliti memilih imagery dan metafora sebagai alat bantu penyampaian materi sistem sirkulasi pada manusia. Penelitian ini merupakan penelitian quasi eksperimen dengan desain Noenequivalent Control Group Design. Model SAVI diterapkan pada kelas eksperimen. Pengumpulan data dilakukan dengan pre-test dan post-test untuk menilai peningkatan dua keterampilan tersebut. Uji yang digunakan adalah uji independent sample t-test dan normalized gain. Hasil penelitian menunjukkan adanya perbedaan signifikan dalam peningkatan keterampilan metakognitif dan berpikir kritis antara peserta didik kelas eksperimen dengan kelas kontrol (0.00 < 0.05). Model SAVI juga cukup efektif untuk meningkatkan dua keterampilan tersebut dengan N-Gain masing-masing sebesar 51.58% dan 62.41%.